HR practices and counterproductive behaviors: a meta-ethnographic study. Issue 7 (2nd November 2020) - Shaffer, Jonathan; Darnold, Todd
Abstract : Purpose: Drawing on the resource-based view (RBV) of the firm and the norm of reciprocity, this paper examines the relationship between high-performance human resources practices (HPHRPs) and employee counterproductive work behavior (CWB), and whether HPHRP interact with coercive control systems to predict these outcomes. Design/methodology/approach: Using meta-ethnographic data collected from 149 organizational ethnographies, the authors test the hypotheses that (a) HPHRP are negatively related to CWB and (b) HPHRP and coercive control interact such that the relationship between HPHRP and CWB is weaker when coercive control is high. Findings: The analysis finds that HPHRP and coercive control interacted such that HPHRP was negatively associated with CWB, but only when coercive control was low. When coercive control was high, the relationship between HPHRP was negated. Practical implications: The results suggest that HPHRP are negatively related to counterproductive behaviors; but when coercive control systems are strong, the potential benefits of HPHRP in terms of reducing CWB may be lost. Originality/value: This study examines the relationship between HPHRP and a comprehensive set of CWB. By examining the interaction between HPHRP and coercive control, the authors add to literature demonstrating that the effects of HPHRP may be dependent on an organization's operational strategy. Finally, our use of meta-ethnographic data offers a methodological approach that may increase the generalizability of our findings.